Effect of light (X = Mg, Si) and heavy (X = Zn) metals on the microstructural evolution and densification of AlCuFeMnTi-X high-entropy alloy processed by advanced powder metallurgy - Chae, Myoung Jin; Lee, Hansung; Sharma, Ashutosh; Ahn, Byungmin (Powder Metallurgy, 2021)
Novel AlCuFeMnTi–X high-entropy alloy (HEA) powder mixture with individual X = Mg, Si, Zn was mechanically alloyed for 45 h and consolidated at 700°C by spark plasma sintering (SPS). The effect of the addition of Mg, Si and Zn was studied on the microstructural evolution, density and microhardness of the developed HEAs. The results demonstrated that milled HEAs were body-centered cubic (BCC) structured (BCC1 and BCC2). The BCC2 fraction was highest in AlCuFeMnTi–Zn followed by AlCuFeMnTi–Si. However, minor Ti, Si and intermetallic compounds (IMC) were observed in AlCuFeMnTi–Mg with BCC1 major phase. After SPS, the alloying improved, and BCC2-rich HEAs were observed for all compositions. An attractive hardness value was obtained in AlCuFeMnTi–Mg due to the dispersed Cu2Mg precipitates in the BCC2/BCC1 matrix followed by AlCuFeMnTi–Si and AlCuFeMnTi–Zn HEA, respectively.
Keywords: Body-centered cubic; Hardness values; Mechanically alloyed; Powder mixtures; densification; High-entropy alloy; mechanical alloying; powder metallurgy; spark plasma sintering